Robotic extralevator excision of a retrorectal giant aggressive angiomyxoma - Scott R. Kelley (Korean Society of Obstetrics and Gynecology, 2018)
Aggressive angiomyxoma (AA) is a very rare mesenchymal tumor most commonly found in the pelvic and perineal regions. For the complete excision of retrorectal tumors, with extension through the levator muscle into the ischioanal space, open anterior and posterior approaches are typically required. Herein, we report our experience with robotic excision of a giant presacral AA with extralevator extension into the ischioanal space and extraction via Pfannenstiel incision, which we found to be technically feasible, efficacious, and safe to perform. Mayo Clinic Institutional Review Board exemption status was obtained for this study.